1967
DOI: 10.1103/physrev.163.1004
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the Levels of Ni and Sn Isotopes by the Quasiparticle Method

Abstract: A modified Tamm-Dancoff approximation, developed in a previous paper, has been applied to even Ni and Sn isotopes. Detailed spectra, £2 transition strengths connecting various levels, and the quadrupole moment of the first excited 2 + level have been calculated and the trends of the results compared with experimental values. The method appears to be fairly satisfactory. It points to the necessity of more reliable information on the effective interaction, active single-particle orbitals, and single-particle rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1968
1968
1981
1981

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The B(E2) values shown in Figure 1 indicate that the levels 0J, 2f, 4]-and 4~-are more strongly collective than has been assumed earlier [1][2][3][4][5][6]. Most of the observed values would be in qualitative agreement with the naive spherical phonon model with the following phonon number assignments: N=4 for 4 +, N=3 for 2 + N=2 for 0 + 2, 2, 2~-and 4~-, N=l for 2+, N =0 for 0+.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The B(E2) values shown in Figure 1 indicate that the levels 0J, 2f, 4]-and 4~-are more strongly collective than has been assumed earlier [1][2][3][4][5][6]. Most of the observed values would be in qualitative agreement with the naive spherical phonon model with the following phonon number assignments: N=4 for 4 +, N=3 for 2 + N=2 for 0 + 2, 2, 2~-and 4~-, N=l for 2+, N =0 for 0+.…”
Section: Discussionmentioning
confidence: 91%
“…The excited states of even Sn nuclei have been studied extensively both experimentally and theoretically as regards their quasi-particle character [1][2][3][4][5][6]. In many recent papers, investigations of two-particle transfer reactions and pairing-vibration excitations have been reported [7 10].…”
Section: Introductionmentioning
confidence: 99%
“…Plastino et al 21, using surfacedelta interaction, and Raj et al 22, employing pairing plus quadrupole interaction (cf. the early work by Kisslinger and Sorensen23), have explicitly calculated the energy spectrum of 118Sn.…”
Section: Discussionmentioning
confidence: 98%
“…In the modified T.D.A. model of Pal et al it is found that an effective charge of 1.35 e is to be used [9] to get good fit to experimental values in the case of Ni and Sn isotopes. In the shell model of heavy even-even nuclei by M. Baranger [10] where the method of linearized equation of motion is used, e"eff ;z:~ e is used to account for the experimental values.…”
Section: Su(3) Representation (~) Given Bymentioning
confidence: 99%